Ecological Apparency Hypothesis and Availability of Useful Plants: Testing different seu values - Ribeiro, João Everthon Silva; Carvalho, Thamires Kelly Nunes; Alves, Carlos Antônio Belarmino; Ribeiro, João Paulo Oliveira; Guerra, Natan Medeiros; Pedrosa, Kamila Marques; Silva, Núbia; Sousa Júnior, Severino Pereira; Nunes, Alissandra Trajano; Souto, Jacob Silva; et al. (Ethnobotany Research and Applications, 2014)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]–> The present study tested the ecological apparency hypothesis in a Brazilian rural community. It used the use value to test the information gained through three types of calculations (UVchange, UVgeneral, UVpotential). A vegetation inventory was performed in two areas near Capivara, Paraíba, Brazil, and 112 informants were interviewed. For the hypothesis test, the Spearman correlation coefficient was used to correlate the phytosociological (vegetation) and ethnobotanical data (use value). The study recorded 25 useful species in the first site and 20 in the second site. Positive correlations were found in the first site, between the UVg to basal area and dominance, and between the UVc and basal area, dominance, and importance value. In the second site, between the UVg and both basal area and dominance and between UVc and basal area, density, and dominance. Apparency explained the local importance of useful plants in construction, technology, and fuel, but was not explanative of medicine. Also, important responses were observed for the different use values. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –>